2016
DOI: 10.1016/j.mvr.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Induced peroxidase and cytoprotective enzyme expressions support adaptation of HUVECs to sustain subsequent H₂O₂ exposure

Abstract: H2O2 mediates autocrine and paracrine signaling in the vasculature and can propagate endothelial dysfunction. However, it is not clear how endothelial cells withstand H2O2 exposure and promote H2O2-induced vascular remodeling. To understand the innate ability of endothelial cells for sustaining excess H2O2 exposure, we investigated the genotypic and functional regulation of redox systems in primary HUVECs following an H2O2 treatment. Primary HUVECs were exposed to two types of H2O2 treatments of both transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…JC‐10 staining, however, clearly indicated a hyperpolarization of the mitochondrial membrane under H 2 O 2 in our experiments. While mitochondrial H 2 O 2 release is triggered by their inner membrane potential , exogenous H 2 O 2 may result in a more complex regulation of the mitochondrial membrane potential . High concentrations (800 µM for 24 hours) of H 2 O 2 have been shown to reduce the ratio of red to green fluorescence of JC‐10, and thus the mitochondrial potential, dramatically in neonatal rat cardiac myocytes .…”
Section: Discussionsupporting
confidence: 69%
“…JC‐10 staining, however, clearly indicated a hyperpolarization of the mitochondrial membrane under H 2 O 2 in our experiments. While mitochondrial H 2 O 2 release is triggered by their inner membrane potential , exogenous H 2 O 2 may result in a more complex regulation of the mitochondrial membrane potential . High concentrations (800 µM for 24 hours) of H 2 O 2 have been shown to reduce the ratio of red to green fluorescence of JC‐10, and thus the mitochondrial potential, dramatically in neonatal rat cardiac myocytes .…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the involvement of NADPH oxidase family has been reported to increase the SODs expression in endothelial cells (Frey, Ushio‐Fukai, & Malik, ). Patel, Chen, and Kavdia ()) reported that SOD2 expression is transient, according to our H 2 O 2 treatment in HUVECs, decreasing after 72 hr compared to other antioxidative enzymes. Regarding catalase, similar effects have been observed in another study with HUVECs, showing its level decreases after H 2 O 2 treatment and increase after a phenolic‐rich extract treatment (Soares et al, ).…”
Section: Discussionsupporting
confidence: 57%
“…Our experiments using the antioxidant NAC showed that NAC had no effect on LPS-or PMA-induced PRDX1 nor on TXNRD1 expression, but did reduce HMOX1 expression suggesting that this is a more redox-sensitive gene (Figure 4). It is known that PRDX1, TXNRD1 and HMOX1 are induced by oxidative stress, but the results presented here suggest that some genes may be more susceptible to changes in redox state than others [39]. A study with HOCl has shown that HMOX1 is induced at lower HOCl concentrations, with the extent of induction similar to the one we observed:…”
Section: Genesupporting
confidence: 76%